2014
DOI: 10.1186/1746-6148-10-159
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical parameters in the blood of Holstein calves given immunoglobulin Y-supplemented colostrums

Abstract: BackgroundIn any calf rearing system it is desirable to obtain healthy animals, and reduce morbidity, mortality, and economic losses. Bovine syndesmochorial placentation prevents the direct transfer of bovine immunoglobulins to the fetus, and calves are born hypogammaglobulinemic. These calves therefore require colostrum immediately after birth. Colostrum is rich in immunoglobulins (Ig) and its consumption results in the transfer of passive immunity to calves. The Ig absorption occurs within the first 12 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…it is absorbed through the intestine of calves, and the concentrations of Alb and TP reflect the immunity of calves and can be used diagnostically [27]. Additionally, serum IgA concentrations, which also reflect the colostrum intake after birth, were not different between the two groups, with both having similar concentrations and decreasing patterns, as previously report [19].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…it is absorbed through the intestine of calves, and the concentrations of Alb and TP reflect the immunity of calves and can be used diagnostically [27]. Additionally, serum IgA concentrations, which also reflect the colostrum intake after birth, were not different between the two groups, with both having similar concentrations and decreasing patterns, as previously report [19].…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, the TP concentrations at Day 0 (starting day of the experiment of each calf) were more than 6.0 g/d l ; the concentrations of Alb, Glb, and the A/G ratio were not significantly different between the two groups during the experimental period. In the colostrum, Alb functions as a transport protein; it is absorbed through the intestine of calves, and the concentrations of Alb and TP reflect the immunity of calves and can be used diagnostically [ 27 ]. Additionally, serum IgA concentrations, which also reflect the colostrum intake after birth, were not different between the two groups, with both having similar concentrations and decreasing patterns, as previously report [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] reported that blood Cu concentrations increased with growth in a study evaluating biomarkers of poor neonatal growth. In addition, as DAO is an enzyme containing copper, its usefulness as a biomarker for Cu deficiency has been reported and it is known that DAO activity is low even in Cu deficiency [ 19 ]. If the blood Cu concentration changes by postnatal days or presence of diarrhea, serum DAO activity may also change with these factors.…”
mentioning
confidence: 99%
“…Provide higher doses of Ig for newborn calves has a direct impact on their immunity system, such as higher levels of circulating Ig, reducing the risk of failure in the passive immunity transfer and consequently lower morbidity and mortality rates (Quigley et al, 2005). Research has shown the benefits of this additional Ig dose, either through higher volumes of colostrum or with supplements (Faber et al, 2005;Quezada-Tristán et al, 2014). The aim of this study was to evaluate the effect of the additional consumption of immune globulins through the feeding of a colostrum supplement associated with high quality maternal colostrum in the transfer of passive immunity, health and performance of newborn Holstein calves.…”
Section: Introductionmentioning
confidence: 99%